2021
DOI: 10.1001/jamanetworkopen.2021.30770
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Perceptions of Mental Health vs Medical Health Plan Networks Among US Adults With Private Insurance

Abstract: IMPORTANCE Ten years after the Mental Health Parity and Addiction Equity Act, patients continue to report insurance-related barriers to specialty mental health care.OBJECTIVES To assess privately insured patients' perceptions of the adequacy of their health plan's provider network (provider network includes physicians, clinicians, other health care professionals, and their institutions that constitute the network), whether practitioners frequently leave plans, and whether practitioner plan participation affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Often, they must go out-of-network, incurring higher health care costs. In a survey of adults with private insurance who have both mental health and medical health plan networks, the investigators reported that participants tended to rate their mental health networks as less adequate compared with their medical health plan networks (Busch & Kyanko, 2021). The inequities of affordable health care are made more prominent when considering socioeconomic and demographic disparities in who may readily access high-quality mental health care and who may not (Cook et al, 2018).…”
mentioning
confidence: 99%
“…Often, they must go out-of-network, incurring higher health care costs. In a survey of adults with private insurance who have both mental health and medical health plan networks, the investigators reported that participants tended to rate their mental health networks as less adequate compared with their medical health plan networks (Busch & Kyanko, 2021). The inequities of affordable health care are made more prominent when considering socioeconomic and demographic disparities in who may readily access high-quality mental health care and who may not (Cook et al, 2018).…”
mentioning
confidence: 99%
“…In the Original Investigation titled “Assessment of Perceptions of Mental Health vs Medical Health Plan Networks Among US Adults With Private Insurance,” 1 published October 22, 2021, an incorrect grant number appeared in the Funding/Support entry of the Article Information section. The grant number should have been given as R21MH109783.…”
mentioning
confidence: 99%